Algae-derived hydrocolloids in foods: applications and health-related issues. Issue 1 (1st January 2021) - Liao, Yu-Chen; Chang, Chia-Che; Nagarajan, Dillirani; Chen, Chun-Yen; Chang, Jo-Shu
ABSTRACT: Hydrocolloids are a class of food additives with broad applications in the food industry to develop structure in food ingredients. Hydrocolloids can be synthetic, plant-based, or animal-based. Increasing consumer awareness has led to the use of natural food ingredients derived from natural sources, making algae-derived hydrocolloids more appealing nowadays. Algae-derived hydrocolloids such as carrageenan, agar, and alginate are widely used in the food industry as thickening, gelling, and emulsifying agents. Carrageenans are sulfated polysaccharides with diverse structural specificities. The safety of carrageenan use in the food industry has been widely debated recently due to the reported pro-inflammatory activities of carrageenan and the probable digestion of carrageenan by the gut microbiota to generate pro-inflammatory oligosaccharides. In contrast, both agar and alginate are primarily nontoxic, and generally no dispute regarding the use of the same in food ingredients. This review provides an overview of the algae industry, the food additives, the algae-derived hydrocolloids, the applications of algae-derived hydrocolloids in food industries, health-related studies, and other sectors, along with future perspectives. Even though differences of opinion exist in the use of carrageenan, it is continued to be used by the food industry and will be used until suitable alternatives are available. In summary, algal hydrocolloids are 'label-friendly' and considered a safe option against synthetic additives. Graphical Abstract: uf0001